Psychology and Phylosophy of Humor (2019)
Humor is considered a universal concept, but, in turn, relative to each culture. From philosophical and psychological theories, this is understood as the product of an incongruity, but also as the reflection of the unconscious desires or the will of power expressed in the act of dominating the weakest. This concept recalls the Dudden Glory of Hobbes. In addition, humor has been understood as a product of evolution that allows us to understand the minds of others and create social bonds that promote the survival of the species. Studies on humor from philosophy and psychology are extensive. And this volume of the collection, “Psychology and philosophy of humor”, delves into the philosophical view of humor and deals with psychological issues related to this subject from current studies that provide a look of child development and graphic understanding of humor; the theory of mind and humor; and humor and understanding of desires. It also deals with elements related to morality, social psychology and the relationship between humor and culture. The great wealth of this work is the actuality of the themes and the development of an almost natural link between humor as a human characteristic and philosophy and psychology.